A Critical Examination of 13-Year Compulsory Education: Early Childhood Education as the Foundation of National Education - Aglesia, Ade Sonnie; Asha, Lukman; Fakhruddin, Fakhruddin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Improving the quality of human resources has become a primary focus in national development towards Indonesia Emas 2045. One of the key strategies is the transformation of the compulsory education policy, which initially mandated nine years of schooling, later expanded to twelve years, and is now directed towards thirteen years with the integration of Early Childhood Education (PAUD). Early childhood education plays a crucial role in shaping children's readiness for primary education while simultaneously reducing literacy gaps from an early age. This article aims to analyze the urgency of expanding compulsory education to thirteen years from the perspective of national human resource development and Indonesia's commitment to Target 4.2 of the Sustainable Development Goals (SDGs) 2030. This study employs a qualitative approach based on literature review of national policy documents, academic studies, and research findings. The results indicate that integrating PAUD into the compulsory education system will strengthen school readiness, enhance equitable access to education, and establish a strong foundation for literacy, numeracy, and character development among Indonesian children. To realize this policy, it is necessary to expand access to quality PAUD services, strengthen national regulations, and foster multi-stakeholder collaboration. Through these efforts, thirteen years of compulsory education will serve as a strategic foundation for developing superior and globally competitive Indonesian human resources.